2014
DOI: 10.14257/ijbsbt.2014.6.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Relevant Factors Affecting the Clinical implementation Competence of Dental Hygienists

Abstract: This study was a descriptive correlation study to increase understanding of, and relationship among job satisfaction, critical thinking disposition and clinical competence of dental hygienists. Survey were undertake by dental hygienists working at the dental clinics located in B City from May 2012 to January 2013. A total of 176 questionnaires, excluding 24 incomplete ones, were analyzed. The influencing factors on clinical competence of dental hygieneists, it appeared that there were positive correlations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
3
1
0
Order By: Relevance
“…In this context, the association with a higher level of satisfaction is also more pronounced in nurses with a broader range of experience and professional capabilities. On this basis, it can be confirmed that higher scores on the evaluated satisfaction factors are proportionally related to the professional capability of TN, which is in line with the findings of Wurgler et al ( 2014 ) and Lee et al ( 2014 ). Namely, Wurgler et al ( 2014 ) found that higher job satisfaction scores were also dependent on the competencies and capability of the employees, while the study by Lee et al ( 2014 ) found strong positive correlations between job satisfaction and the professional capability of nurses.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this context, the association with a higher level of satisfaction is also more pronounced in nurses with a broader range of experience and professional capabilities. On this basis, it can be confirmed that higher scores on the evaluated satisfaction factors are proportionally related to the professional capability of TN, which is in line with the findings of Wurgler et al ( 2014 ) and Lee et al ( 2014 ). Namely, Wurgler et al ( 2014 ) found that higher job satisfaction scores were also dependent on the competencies and capability of the employees, while the study by Lee et al ( 2014 ) found strong positive correlations between job satisfaction and the professional capability of nurses.…”
Section: Discussionsupporting
confidence: 90%
“…On this basis, it can be confirmed that higher scores on the evaluated satisfaction factors are proportionally related to the professional capability of TN, which is in line with the findings of Wurgler et al ( 2014 ) and Lee et al ( 2014 ). Namely, Wurgler et al ( 2014 ) found that higher job satisfaction scores were also dependent on the competencies and capability of the employees, while the study by Lee et al ( 2014 ) found strong positive correlations between job satisfaction and the professional capability of nurses. The study results by Francis ( 2015 ) confirm that the higher professional capability of employees has a proportionate impact on the level of job satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations